Clinical profiles of neonates born to mothers with COVID-19 - Ambili Susan Jacob; Mohammed MTP; Reetha Gopinath; Binoo Divakaran; Tariq Harris (Indonesian Pediatric Society, 2021)
Background The risk of congenital infections in neonates born to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected mothers and those breastfed by infected mothers remains largely unknown. Objective To describe the outcomes and clinical features of neonates born to mothers infected with SARS-CoV-2 during pregnancy, to follow up neonates who were positive for SARS-CoV-2 at the time of delivery for a period of 1 month, and to identify potential risk factors associated with disease transmission. Methods This prospective observational study on neonates born to SARS-CoV-2-infected mothers between June 2020 and January 2021 was carried out after getting written informed consent in a tertiary care government hospital (Government Medical college Kannur, North Kerala, India). The clinical and demographic characteristics of infected mothers were reviewed. Neonates were tested for SARS-CoV-2 infection within 24 hours of birth, with repeat testing on day 5 for those who were negative at birth. The demographic and clinical characteristics as well as potential risk factors for disease transmission in these neonates were evaluated. Results A total of 342 neonates (95.3%) were tested for SARS-CoV-2 infection at birth. Rooming-in and breastfeeding was practiced in 75% of at-risk neonates. Fifty neonates tested positive for SARS-CoV-2 infection at birth (14.3%); 293 neonates who tested negative at birth remained so on day 5, except one baby isolated with a caretaker who also tested positive, indicating postnatal infection. There was no statistically significant increased risk of infection in neonates born to SARS-CoV-2-positive mothers compared to those born to mothers who had already become negative at delivery. Mild symptoms were present in 8% of positive neonates. On one-month follow up, all neonates were well and gaining weight. Conclusion Vertical transmission, in particular transplacental, may be possible in SARS-CoV-2-infected mothers. Maternal infection at the time of delivery is not a predictor for increased vertical transmission compared to mothers whose infections had resolved prior to delivery. Breastfeeding with appropriate hygiene measures is not a risk factor for horizontal transmission.